Content Analysis of Corporate Social Responsibility Communication in Sustainability Reports - Lestari, Ayu Ambang; Sayuti, Alfian; Ardiansyah, Lalu Yayan (EAJ (Economic and Accounting Journal), 2026)
The purpose of this study is to analyze the Corporate Social Responsibility (CSR) content contained in sustainability reports and to determine the extent to which PT Perusahaan Listrik Negara (PLN) conveys information related to economic, environmental, and social aspects. This study uses both qualitative and quantitative content analysis, considering disclosure indicators that refer to the Global Reporting Initiative (GRI) standards. Data were taken from PT PLN's 2022-2024 sustainability reports and analyzed to assess the extent of information disclosure and the company's consistency in addressing sustainability issues. The results show that PT PLN's CSR disclosures have fluctuated over the past three consecutive years, with the most frequently disclosed aspect of its social responsibility being the environmental aspect. This indicates that the company is increasingly concerned with environmental issues resulting from its operational activities. These findings indicate that the company is increasingly recognizing the importance of transparency and accountability in sustainability reporting. This research is expected to contribute to the development of CSR reporting practices and serve as a reference for stakeholders in assessing the company's commitment to sustainable development.